Application of the Concept of Hybrid Contracts Pawning and Gold Investment in Sharia Banking (Case Study of Indonesian Sharia Bank KCP Majalengka Duchy) - Nungki, Nungki Pahrussadi; Nana, Nana Herdiana; Yoyok, Yoyok Prasetyo (Zona Law And Public Administration Indonesia, 2024)
The practice of gold pawning and gold investment has been widely practiced by Bank Syariah Indonesia. In this case, the author chose Bank Syariah Indonesia (BSI) Kadipaten Sub-Branch Office, Majalengka as the object of writing, namely to see the practice of gold pawning and gold investment carried out. In this study, the authors set two problem formulations, namely how the implementation of Hybrid Contracts on gold pawning and gold investment at Bank Syariah Indonesia (BSI) Kadipaten Sub-Branch Office, Majalengka and how Islamic law views the implementation of Hybrid Contracts on gold pawning and gold investment at Bank Syariah Indonesia (BSI) Kadipaten Sub-Branch Office, Majalengka. In the process of writing this paper, the author uses qualitative research methods and is descriptive qualitative. The data collection technique uses interview techniques, sources from related books and journals, after research, that BSI Kadipaten conducts 3 contracts, namely rahn contracts, qardl contracts, and ijarah contracts in gold pawning practices and 2 contracts for gold investment practices, namely murabahah (sale and purchase) and rahn (pawn) contracts. From the results of the research conducted, the researcher concluded that the implementation (practice) of gold pawning at Bank Syariah Indonesia (BSI) Kadipaten Sub-Branch Office, Majalengka has fulfilled the pillars and conditions of each contract used. So that in the view of Islamic law the implementation of gold pawn financing at Bank Syariah Indonesia (BSI) Kadipaten Sub-Branch Office, Majalengka has been valid and may be carried out and there is no violation of sharia and there is nothing different from the gold pawn standard at Bank Syariah Indonesia (BSI) Kadipaten Sub-Branch Office, Majalengka, while the legal basis of Islamic gold investment is, Law No. 21 of 2008 concerning Islamic Banking, and DSN-MUI Fatwa No. 77/DSN-MUI/VI/2010 concerning Cashless Gold Buying and Selling. Circular Letter of BI (SE BI) No. 14/7/DPBS dated February 29, 2012 on Gold Collateralized Qardh Products for Islamic Banks and Islamic Business Units (UUS). DSN-MUI fatwa No. 25/DSN-MUI/III/2002 dated June 26, 2002 on Rahn and DSN MUI Fatwa No. 26/DSN-MUI/III/2002 dated March 28, 2002 on Gold Rahn. There are two opinions regarding the validity of Islamic gold investment, there are jumhur scholars who allow and some prohibit. Translated with DeepL.com (free version)